Pengembangan Media Diaroma Terhadap Hasil Belajar Siswa Pada Materi Siklus Air di SMP Negeri 4 Kota Bengkulu - Sari, Meirita; Yunilarosi, Elvida sari; Laili, Ummiy Fauziyah; Yulita, Nourma (CV. Cendekiawan Muda Sriwijaya, 2024)
This study aims to explore the development of diorama media to improve student learning outcomes on the water cycle topic at SMP Negeri 4 Kota Bengkulu. The diorama media is used as an interactive and visual learning tool to enhance students' understanding of the water cycle concept. The research method applied is Research and Development (R&D). The study sample comprises two randomly selected classes, an experimental class using diorama media and a control class using conventional methods. Data collection instruments include a pre-test and post-test to assess learning outcomes before and after the intervention. Data were analyzed using a t-test to compare learning outcomes between the two groups. The analysis results showed that media expert validation I reached 90.57%, media expert II 93.7%, material expert I 92.5%, and material expert II 89.6%. Test results indicated a significant difference in learning outcomes between the experimental and control classes, with students who learned through diorama media showing higher learning gains compared to those who used conventional methods. Diorama media often captures students' attention due to its visually engaging presentation and ability to represent abstract concepts visually. Therefore, the use of diorama media can enhance the effectiveness of learning in the water cycle topic.